Epistemologi Pendidikan Islam dan Transformasi Pesantren: Menjaga Tradisi di Tengah Tantangan Modernisasi - Tsamrotul Fuada; M. Yunus Abu Bakar; Zainur Arifin (IIQ An Nur Yogyakarta, 2026)
Pesantren, as traditional Islamic educational institutions, face various challenges posed by modernization such as globalization, digitalization, and the demands of the national curriculum which have the potential to shift the academic identity and educational traditions of pesantren. This study aims to analyze the role of the epistemology of Islamic education in the transformation process of pesantren and to identify the strategies pesantren employ to preserve their traditions amid the demands of modernization. The study employs a descriptive qualitative approach using a literature review method. Data were obtained through the search and selection of scholarly sources, including books, journal articles, and documents related to the epistemology of Islamic education and the transformation of pesantren. Data analysis was conducted using content analysis, following the stages of data reduction, theme grouping, interpretation of meaning, and systematic conclusion-drawing. The results of the study indicate that the epistemology of Islamic education serves as a crucial foundation for maintaining a balance between preserving pesantren traditions and the need to adapt to contemporary developments. The transformation of pesantren can be achieved through the integration of traditional and modern curricula, the strengthening of character and moral education, the implementation of contextual learning, the promotion of religious moderation, and the preservation of the collective culture of pesantren. These findings emphasize that modernization should not be understood as the elimination of tradition, but rather as a process of adaptation that remains grounded in the values.